Efficacy of topical heparin spray on donor site wound healing after split thickness skin grafting - Faraz Adil; Mahak Ali Memon; Faisal Akhlaq Ali Khan; Asadullah Awan; Saad Uddin Siddiqui; Farhan Zahid Piprani; Kulsoom Zareen (Scientific Reports)
Abstract All wounds that cannot be closed primarily needs skin coverage earliest to prevent form infections. Skin graft provides earliest and easiest wound coverage, but produces another wound, i.e. donor site wound. This study was conducted to see healing time efficacy in donor site wounds. Study was designed as prospective and randomized control study, in the Department of Plastic and Reconstructive Surgery at Civil Hospital Karachi, included 60 patients who underwent split thickness skin grafting. From the next day of surgery heparin and conventional dressings groups were made and dressing was done daily till seventh postoperative day. Data in form of questionnaire and photographs were recorded. This study was a self-controlled trial, therefore every trial participant served as his/her own control. The results of the analysis showed a decrease in soakage of dressing and a reduction in itching at intervention site. In regard to wound size, 40% of participants showed a reduction in wound size and only 20% showed no improvement at interventional half. During 7days, 81.67% of participants showed improvement in edema at intervention half. The study showed heparin irrigation resulted in better wound healing by reducing pain, edema, faster healing and reducing soakage of dressings. Trial registration The study was approved by Institutional Review Board of Dow University of Health Sciences and was registered at Clinical Trials.gov (ID NCT04613336) on 13/07/2021.